Posttraumatic true aneurysm of the superficial temporal artery - Apoorva Vempati; Sandeep Mahapatra; Pramod Kumar Pamu (Indian Journal of Vascular and Endovascular Surgery, 2021)
Most superficial temporal artery (STA) aneurysms are pseudoaneurysms that occur following a trivial trauma to the temporal region. True aneurysms of the STA are very rare. They occur usually due to congenital defects in vessel wall or atherosclerotic degeneration. We report a case of true aneurysm of the STA following trauma which is exceedingly rare. A 23-year-old male presented with painless swelling in front of the right ear for 4 months with a history of trauma to the right temporal region. Examination revealed a painless pulsatile mass of 4 cm × 3 cm size, and the diagnosis was supported by Doppler ultrasound and magnetic resonance imaging. Surgical excision was done. Histological examination showed all the three layers of the arterial wall to be intact, confirming a diagnosis of true aneurysm of the STA.